2010
DOI: 10.1093/occmed/kqq040
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and mortality related to alcohol, drugs and sexual habits

Abstract: Our findings highlight major differences between occupations in mortality from diseases and injuries caused by alcohol, sexual habits and drug abuse. Priorities for preventive action include alcohol-related disorders in male seafarers and drug abuse in construction workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…There are, however, counter-examples of femaledominated occupations related to unfavourable drinking cultures, for example, the sex industry or gastronomy.The latter has repeatedly been shown to be related to elevated levels of alcohol consumption and associated harm [50,51].…”
Section: Influence Of the Measure Of Sesmentioning
confidence: 98%
“…There are, however, counter-examples of femaledominated occupations related to unfavourable drinking cultures, for example, the sex industry or gastronomy.The latter has repeatedly been shown to be related to elevated levels of alcohol consumption and associated harm [50,51].…”
Section: Influence Of the Measure Of Sesmentioning
confidence: 98%
“…These include smoking level, alcohol consumption and lack of leisure-time physical activity (Carel, Carmil, & Keinan, 1990). Analysis of national data for England and Wales indicates that seafarers are among the groups of occupations with the highest mortality from alcohol-related diseases and injuries (Coggon, Harris, Brown, Rice, & Palmer, 2010). The results of a stratified survey of French seafarers (Fort, Massardier-Pilonchery, & Bergeret, 2009) confirmed that alcohol and nicotine consumption is a major public health issue in seafarers.…”
Section: Physical Health Of Seafarers and Lifestyle Factorsmentioning
confidence: 98%
“…Recent evidences indicate that non-alcoholic fatty liver disease is the main common reason of liver diseases in Iran [35]. High rates of alcohol-related diseases in seamen have been reported in other countries as well so that it is recommended mentioned problem should be a priority for preventive actions in maritime industry [36,37].…”
Section: Discussionmentioning
confidence: 99%